The Purpose of the Sheikh Ubeydullah Nehrî Revolt - Kılıç, Avni (The Scientific Journal of Cihan University– Sulaimaniya, 2022)
The 19th century was the era in which empires began to disintegrate, concepts such as nationality and ethnic belonging gained importance, and divisions based on ethnic belonging were experienced. Separations from multinational empires has occurred and new nation-states have begun to form in Europe as well as outside Europe. The multinational structure of the Ottoman Empire was also affected by these changes. The Ottoman government, which wanted to prevent separation from the empire, implemented a series of reforms in order to strengthen the central government, and eventually tried to strengthen the center by eliminating the autonomous Kurdish mirs. With the disappearance of mirs from the stage of history, another power, sheikhs, began to fill their place. In this period when chaos and turmoil prevailed in the region, Sheikh Ubeydullah from Hakkari, one of the sheikhs of the Sadatê Nehrî, gained importance in region. Sheikh Ubeydullah complained about the mismanagement of the Ottoman and especially the Iranian government in 1880, and finally, he led an uprising to put an end to this bad course with his own methods. Although the uprising was not successful for the sheikh, the purpose of the sheikh is still debated in academic circles today. While some perceived the sheikh as a Kurdish nationalist and claimed his aim was to establish a Kurdish state, and others claimed that the sheikh's movement had an Islamic/Sunni character and was trying to connect Iranian Kurdistan to the Ottoman Empire. The degree of reality of these claims, what the sheikh aimed for in his revolt against Iran and the Ottoman Empire, were tried to be explained by examining the correspondence and reports of the western missionary and consular officers working in the region, and especially the Ottoman official authorities.